Shalom, the spirit and pentecostal conversion: a practical-theological study - Milton, Grace (Global Pentecostal and charismatic studies, 2015)
Grace Milton presents a uniquely practical-theological model of Pentecostal conversion, centered on empirical data from a congregational case study. Pentecostal-Charismatic conversion is commonly equated with a dramatic, “Damascus road” type event, which directly opposes prevailing theories within the social sciences that conversion is a more gradual process over time. This raises the question, how far do these Pentecostal stereotypes reflect lived experience?0In this book, for the first time, the experiences and beliefs of ordinary Pentecostal believers are drawn into conversation with conversion theories from the human sciences (sociology, psychology and anthropology) and theology. The result is a distinctly Pentecostal model of conversion, which interprets religious transformation through the theological lens of Shalom